Treatment of rosacea with upadacitinib and abrocitinib: case report and review of evidence for Janus kinase inhibition in rosacea - Zhang, Ting; Liu, Xu; Zhang, Lu; Jiang, Xian (Frontiers in Immunology, 2024)
Introduction: Conventional rosacea treatments are not uniformly pervasive, and the adverse reactions can potentially constrain their utility. The clinical use of JAK1 inhibitor upadacitinib and abrocitinib in the treatment of refractory rosacea have rarely been explored.We presented the two cases of patients who received JAK1 inhibitor upadacitinib and four cases of patients who received JAK1 inhibitor abrocitinib for the treatment of refractory rosacea.Discussion: JAK1 inhibitor upadacitinib and abrocitinib may be promising medical options for patients with refractory rosacea. However, the long-term safety and efficacy of upadacitinib and abrocitinib require prospective controlled studies to assess more comprehensively.